(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The research aims to generate a theoretical approach on research in the classroom to build knowledge from a complex referential approach. In particular its extension. Describe what teachers understand and research student in the classroom to build knowledge from their practice teaching. Understand the thought processes that emerge from the experiences of faculty and student research in the classroom as a dynamic and complex for the construction of knowledge. Interpret the meanings that emerge from experiential situations of teachers and students about research in the classroom for the construction of knowledge. Grounded Theory of Complexity and to support the principles of complex thinking. The seven knowledge of education of the future and Constructivism. Taking regional and national history. As units of analysis identifies research in the classroom. Construction of knowledge from a complex referential approach. Qualitatively focused. Using ethnographic methods, supported in Hermeneutics, so know and understand the experiences of key informants and assign meaning. The strategy to address it are three scenarios: Scenario I: Conceptual, Stage II: Interviews, Stage III: Final Theory Approach. Data collection techniques used in-depth interviews. The information provided by the voices of key informants was reduced to categories and triangulated once, contributed to emergence theory approach to conducting research in the classroom and serve as a strategy for the construction of knowledge at university level.